Effect of Dichloromethane-Methanol Extract and Tomentin Obtained from Sphaeralcea angustifolia Cell Suspensions in a Model of Kaolin/Carrageenan-Induced Arthritis - del Pilar Nicasio-Torres, María; Serrano-Román, Jade; Pérez-Hernández, Juanita; Jiménez-Ferrer, Enrique; Herrera-Ruiz, Maribel (Planta Medica International Open, 2017)
Cell suspension cultures from Sphaeralcea angustifolia produce compounds with anti-inflammatory activity, including scopoletin, tomentin, and sphaeralcic acid. Antiarthritic activity of scopoletin isolated from S. angustifolia and Erycibe obtusifolia wild plants was demonstrated in a complete Freud’s adjuvant-induced arthritis model. In this project, the dichloromethane-methanol extract and tomentin isolated from S. angustifolia cell suspension were evaluated in mice using a kaolin/carrageenan-induced arthritis model. After 9 days of treatment, the anti-inflammatory effect of S. angustifolia dichloromethane-methanol extract was 72% at a dose of 100 mg/kg, a recovery of 55% was observed with methotrexate (5.0 mg/kg), and the anti-inflammatory effect for tomentin was dose-dependent with a median effective dose of 10.32 mg/kg. The concentration of pro-inflammatory cytokines interleukin-1β and tumor necrosis factor alpha in the left joint of groups treated with S. angustifolia dichloromethane-methanol extract and tomentin at different doses was significantly lower than that detected in the group damaged with kaolin/carrageenan, and the concentration of interleukin-10 and interleukin-4 (anti-inflammatory cytokines) was significantly higher. The drop in mean body weight of mice treated with methotrexate (−4.34±0.47 g) was higher in comparison with the kaolin/carrageenan group (−2.40±0.29 g). On the other hand, the mean body weight of mice treated with S. angustifolia dichloromethane-methanol extract (−1.19±0.17 g) was similar, and mice treated with tomentin (0.19±0.11 g) was lower. The dichloromethane-methanol extract and tomentin isolated from S. angustifolia diminished joint edema induced by kaolin/carrageenan, possibly by acting as an immunomodulatory of the inflammatory response.
Keywords: Sphaeralcea angustifolia; Malvaceae; anti-inflammatory; arthritis; coumarins; scopoletin.